1997
DOI: 10.1007/bf01834068
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of pedicle screw insertion: A prospective CT study in 30 low back patients

Abstract: A prospective study of the accuracy of titanium pedicle screw placement in 30 low back operations was performed. The postoperative plain radiographs and CT reformation images were evaluated by two independent radiologists. Thirty-two out of 152 screws (21%) perforated the pedicle cortex. One-tenth of the perforations was detected with conventional radiography. In ten patients (33%) all the screws were located within the pedicle. The clinical significance of this study lies in the finding that pedicle perforati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(101 citation statements)
references
References 10 publications
3
93
0
5
Order By: Relevance
“…Biomechanical studies have shown that pedicle screws provide increased rigidity and construct stiffness compared to other posterior fixation techniques [32,33]. It is a technically demanding procedure and studies have shown an alarmingly high rate of screw misplacement varying between 21 and 39.8% with conventional insertion techniques [1][2][3]. The misplaced screws can cause three types of complications, namely neurological, vascular and mechanical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanical studies have shown that pedicle screws provide increased rigidity and construct stiffness compared to other posterior fixation techniques [32,33]. It is a technically demanding procedure and studies have shown an alarmingly high rate of screw misplacement varying between 21 and 39.8% with conventional insertion techniques [1][2][3]. The misplaced screws can cause three types of complications, namely neurological, vascular and mechanical.…”
Section: Discussionmentioning
confidence: 99%
“…The reported pedicle screw misplacement in historical spinal literature can be as high as [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].8% [1][2][3], but only a small number leads to complications (neurological, vascular or visceral injuries). But these complications can be potentially life and limb threatening.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of our analysis, breach is defined as a pin with more than 25% of its diameter residing outside and medial, inferior, or superior to the pedicle 10 and/or a pin protruding more than 2 mm. 4,8 Independent analyses of placement of Steinmann pins were performed by 2 fellowship-trained spine surgeons and a neuroradiologist. Analysis of the CT scan included recording the following data for each pin: 1) spinal level, noting laterality, and approach used; 2) whether the pedicle had been breached (yes/no); and 3) the extent of pin protrusion for any breached pedicles (i.e., pin diameter or millimeters).…”
Section: Methodsmentioning
confidence: 99%
“…These scans were reviewed by an independent reviewer (AFS) Perforations < 2mm on CT scan are thought not to be associated with clinical sequelae, 22 and other authors report perforations as large as 4mm being associated with no problems. 23 Gertzbein and Robbins 24 reported an incidence of medial cortical penetration up to 8 mm with two minor neurological injuries. They hypothesize a 4mm safe zone, which includes 2mm of epidural space and 2mm of subarachnoid space.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using a postoperative CT scan reviewed by independent or blinded reviewers show higher rates of perforation than those determined by radiograph. Laine et al 23 reviewed 30 low back operations. In this series of 152 pedicle screws, 32 screw perforations (21%) were detected by CT scan, whereas only 3 were detected by plain radiographs.…”
Section: Descriptores: Fluoroscopía Tornillos óSeos; Columna Vertebrmentioning
confidence: 99%